An Analysis Of English For Specific Purpose (ESP) Textbook For Maritime And Fisheries Students Published By Indonesian Ministry Of Education And Culture - Vischa Mansyera Pratama; Herdi Herdi; Violintikha Harmawan Violintikha Harmawan; Rahmi Fadilah Rahmi Fadilah; Ramanda Rizky Ramanda Rizky (Al-Makki Publisher, 2023)
This research analyze and describe the quality of the English textbook in term of the activities provided by this book. The object of this research was the Bahasa Inggris Maritim dan Perikanan textbook for 10th grade students published by the Indonesian Ministry of Education and Culture. The current research was conducted to analyze the need of suitable and comprehensive learning materials for English for Specific Purpose (ESP) Class. This research used an analysis format as the instrument to guide the researcher in analyzing the English textbook. The analysis format contained of six categories which was made based on the principles of a good textbook proposed by the experts those are readiness activities, experiential activities, intake response activities, development activity 1, input response activity, and development activity 2. The result of this research showed that this English textbook for maritime students published by the Indonesian Ministry of Education and Culture can be categorized as good textbook since all of the criteria was found in this book. Meanwhile, there are two categories that were rarely found and need to be revised in this textbook; development activity 1 and development activity 2. However, the other criteria had enough number as the activities provided by this book.